Queensland Microbial Keratitis Database: 2005–2015. Issue 10 (5th January 2019) - Green, Matthew; Carnt, Nicole; Apel, Andrew; Stapleton, Fiona
Abstract : Aims: To estimate the incidence of culture-positive microbial keratitis in Queensland and analyse trends in the organisms and their sensitivities cultured from corneal scrapes, especially low-incidence organisms. Methods: Retrospective multicentre case series of all positive corneal scrapes in Queensland, Australia between 2005 and 2015. Pathology organisations in Queensland were identified by online and local directory search and agreed to participate. Digital records of scrapes provided patient demographics and culture and susceptibility results. Trends in the incidence, organisms and sensitivities were monitored with linear regression. The yearly incidence of microbial keratitis was estimated from the Queensland population. Results: The included corneal scrapes totalled 3182, while 1006 were excluded. The included scrapes yielded 4111 organisms. Pseudomonas aeruginosa was the most common single isolate (729, 17.7%), although Gram-positive organisms were more common overall (2737, 66.6%). Fungal organisms were cultured in 6% of cases, while Acanthamoeba comprised only 1% of records. Bacterial organisms were sensitive to all recorded antibiotics in 89% of all isolates and none of the reported antibiotics showed a decreasing trend in susceptibility. The incidence of protozoal isolation decreased over time (p=0.055). Cultures positive for yeasts showed a linear increase in incidence (p=0.045) while moulds showed a spike in incidence in 2010–2012 (p=0.0008). Conclusion: The estimated incidence of microbial keratitis was 0.66 cases per 10 000 people, the rate of antibiotic susceptibility is high and stable, the incidence of keratitis secondary to protozoa is likely to be decreasing while the incidence of keratitis culturing yeast is increasing.